The Township, the Pregnant Girl and the Church: Community Dynamics, Gender and Social Control in Early Nineteenth-century Scotland. Issue 1 (May 2019) - Ritchie, Elizabeth
Abstract : In 1814 in a small Highland township an unmarried girl, ostracised by her neighbours, gave birth. The baby died. The legal precognition permits a forensic, gendered examination of the internal dynamics of rural communities and how they responded to threats to social cohesion. In the Scottish 'parish state' disciplining sexual offences was a matter for church discipline. This case is situated in the early nineteenth-century Gàidhealtachd where and when church institutions were less powerful than in the post-Reformation Lowlands, the focus of most previous research. The article shows that the formal social control of kirk discipline was only part of a complex of behavioural controls, most of which were deployed within and by communities. Indeed, Scottish communities and churches were deeply entwined in terms of personnel; shared sexual prohibitions; and in the use of shaming as a primary method of social control. While there was something of a 'female community', this was not unconditionally supportive of all women nor was it ranged against men or patriarchal structures.